Relationship between School Characteristics and Students’ Academic Aspiration: The Case of Public Secondary Schools in Laikipia County, Kenya - Kingori, Eshphan Waweru; Kiumi, John Kanjogu; Kingori, Isaac Wanjohi (Indonesian Journal of Educational Counseling, 2019)
Students’ academic performance is dependent on many factors, the study focused on academic aspiration which was construed as a critical correlate of academic achievement. The study presumed that knowledge on academic aspiration may help to explain why students could be performing lowly in KCSE examination. To this end, the study sought to find out whether or not aspiration would differ across schools with different characteristics. Two schools characteristics were focused by the study: whether a school was single sex or coeducational on the one hand, and level of school’s performance in KCSE examination.  Using ex post facto research design, data were collected using personally delivered questionnaires from 375 secondary schools students in the study locale and subsequently analyzed using χ2 test at .05 alpha level. The findings indicated that level of academic aspiration was higher in boys’ only schools compared with girls’ only and coeducational schools. The revealed differential levels of academic aspiration was statistically significant (χ2= 5.620; df= 6; p< .05) and relatively strong (Cramer’s V= 0.205). The results also indicated that students’ academic aspiration increased with increase in school’s level of KCSE examination. The differential effect of school’s KCSE examination performance status on academic aspiration was similarly statistically significant (χ2= 12.78; df= 15; p< .05) and very strong (Cramer’s V=0.811).